Analisis Persepsi Pelaku Usaha Mikro Kecil dan Menengah Atas Penyusunan Laporan Keuangan Berdasarkan SAK EMKM pada Pelaku UMKM Kecamatan Medan Marelan - Novi Anggelia Tratama; Maya Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine and analyze the perceptions of MSME actors in Medan Marelan District regarding the preparation of financial reports based on SAK EMKM. Data collection was carried out by distributing questionnaires to 50 MSMEs in Medan Marelan District. The research approach uses descriptive research. Next, the data analysis used is descriptive statistical analysis, using a Likert scale to measure respondents' perceptions. The research results show that MSME actors in Medan Marelan District as a whole have not implemented SAK EMKM so that the resulting financial reports are still not fair and not comparative. Judging from the results of the data analysis, it can be concluded that the perception of MSME actors regarding the use of accounting information can help MSME actors survive and even excel in running their businesses amidst increasingly difficult competition, and accounting can provide the information needed to make decisions for business continuity in the future. front. Although indicators of understanding and readiness are still low.